Enriching gifted and talented students via smart tablets - Ibrahim, Abdel Rahman; Saleh, Nik Salida Suhaila Nik; Yusoff, Nik Mohd Rahimi Nik; Kamarudin, Mohd Yusri; Zakaria, Zulkarnin (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA